Investigation of the tribofilm formation of HiPIMS sputtered MoSx thin films in different environments by Raman scattering - Tillmann, Wolfgang; Wittig, Alexandra; Stangier, Dominic; Thomann, Carl-Arne; Moldenhauer, Henning; Debus, Jörg; Aurich, Daniel; Brümmer, Andreas (Technische Universität Dortmund, 2019)
Understanding the generation of third body particles and their contribution to the formation of tribofilms of MoSx thin films is still challenging due to a large number of influencing factors. Besides the structure of the as-deposited MoSx films, the environment and the conditions during the Ball-on-disk tests affect tribofilms and thus the friction. Therefore, the influence of the surface pressure and sliding velocity in air, argon and nitrogen environments on the generation of the third body particles and the tribofilm formation of randomly oriented MoSx films is investigated. A high surface pressure is one major factor to achieve low friction, especially under humid conditions, which is important considering the use in industrial applications, for example dry-running screw machines. However, the mechanisms leading to that frictional behavior are still affected by the surrounding environment. While low friction is caused by a more extensive tribofilm formation in air, in argon and nitrogen, large size third body particles dispensed all over the contact area contribute to a lower friction. Raman scattering reveal a different chemistry of these particles reflected in the absence of laser- or temperature-induced surface oxidation compared to the as-deposited film and the wear track. The Raman scattering results are discussed with respect to the wear particle size, its chemical reactivity and strain-induced bonding changes.
Lubricants;7(11)
Keywords: MoSx; Third body particles; Tribological behavior; Surface pressure; Sliding velocity; Environment; Raman scattering; 620; 670; MOS; Tribologie; Flächenpressung; Oberflächenverstärkter Raman-Effekt